2020
DOI: 10.3390/v12091006
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Antiviral Research Database (CoV-RDB): An Online Database Designed to Facilitate Comparisons between Candidate Anti-Coronavirus Compounds

Abstract: Background: To prioritize the development of antiviral compounds, it is necessary to compare their relative preclinical activity and clinical efficacy. Methods: We reviewed in vitro, animal model, and clinical studies of candidate anti-coronavirus compounds and placed extracted data in an online relational database. Results: As of August 2020, the Coronavirus Antiviral Research Database (CoV-RDB; covdb.stanford.edu) contained over 2800 cell culture, entry assay, and biochemical experiments, 259 animal model st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 134 publications
5
84
0
Order By: Relevance
“…The spike (S) protein of SARS-CoV-2 is the primary target of neutralizing antibodies (NAbs) (Fig 1A). Therefore, NAbs against SARS-CoV-2 that have either been deployed for therapy or are in advanced stage trials, for the most part, either target the receptor-binding domain (RBD) or the N-terminal domain (NTD) of the spike glycoprotein (Fig 1A and 1B) [1,2]. The S protein exists in different conformations within the host, and their nomenclatures are based on the position of RBD protein-an "up" or "down" position (Fig 1B).…”
Section: Primary Targets Of Sars-cov-2 Therapeutic Neutralizing Antibodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The spike (S) protein of SARS-CoV-2 is the primary target of neutralizing antibodies (NAbs) (Fig 1A). Therefore, NAbs against SARS-CoV-2 that have either been deployed for therapy or are in advanced stage trials, for the most part, either target the receptor-binding domain (RBD) or the N-terminal domain (NTD) of the spike glycoprotein (Fig 1A and 1B) [1,2]. The S protein exists in different conformations within the host, and their nomenclatures are based on the position of RBD protein-an "up" or "down" position (Fig 1B).…”
Section: Primary Targets Of Sars-cov-2 Therapeutic Neutralizing Antibodiesmentioning
confidence: 99%
“…The class IV NAbs do not overlap with ACE2 binding site and bind conserved region in RBD (core I region) or RBD in "up" conformation only (core II region) (Fig 1B and 1C). A complete description of these 4 classes of RBD-dependent mAbs is shown in Fig 1C . Class IV core I region-dependent NAbs have broad neutralizing activity against SARS-CoV-2, its variants, and other related coronaviruses [1][2][3]7]. Very recently, NAbs targeting new epitopes on the S2 domain (stem helix region) of spike have also been identified that are broadly neutralizing, i.e., neutralize SARS-related and other human coronaviruses (hCoVs) [8][9][10][11].…”
Section: Primary Targets Of Sars-cov-2 Therapeutic Neutralizing Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinicaltrials.gov [18] was searched on 14th December 2020 using key words COVID, SARS-CoV-2 and ivermectin to identify studies. The WHO International Clinical Trials Registry Platform (ICTRP) was accessed via the COVID-NMA Initiative's mapping tool, updated to 9th December 2020, [19] and Stamford University's Coronavirus Antiviral Research Database (CoV-RDB), updated to 15th December 2020, [20] to identify additional trials listed on other national, and international registries.…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
“…The SARS-CoV-2 receptor binding domain (RBD) is the dominant target of the neutralizing response during infection 7,[10][11][12][13] . Consequently, the overwhelming majority of monoclonal neutralizing antibodies isolated thus far from infected individuals, immunoglobulin libraries, or immunized animal models, target this region 10,11,13,14 . These antibodies can be broadly divided into four main classes 15 , of which class 1 and class 2 antibodies target site I 10 epitopes that overlap with the angiotensin converting enzyme 2 (ACE2) receptor binding site.…”
Section: Introductionmentioning
confidence: 99%